Addressing the Challenges of Learning English in a Rural School - Daulay, Sholihatul Hamidah; Daulay, Nurika Khalila; Sari, Winda; Arlina; Nurani, Siti (PEBSAS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
In rural educational institutions, various obstacles impede the acquisition of the English language. The difficulties experienced in learning English within these rural schools are intricately linked to the environmental conditions surrounding the students, the proficiency of the English instructor, and the overall educational atmosphere. This research examined the obstacles encountered by students engaged in English language studies in rural educational settings. Two English educators who participated in this qualitative research served as respondents. The results of this investigation indicate that the pursuit of English language proficiency in rural schools continues to encounter a multitude of challenges. The process of learning English proved to be arduous for several reasons, including the students' diminished motivation towards the subject and the insufficient external support, such as encouragement from both parents and the broader community.